Herodotus, Cambyses, and the Crossword Puzzle - Brock, Roger (Histos, 2019)
Herodotus depicts a world full of puzzles including, but not limited to, oracles and dreams, which require solution: this calls for a range of interpretative strategies and for a constant sceptical mental alertness. Often, understanding is reached in a moment of insight, something to which Herodotus seems peculiarly attentive among writers of history, and it is suggested that, like the perception of parallels and patterns in past events, this reflects some fundamental cognitive processes.